2021
DOI: 10.1111/ijcp.14800
|View full text |Cite
|
Sign up to set email alerts
|

Can prognostic nutritional index predict mortality in intensive care patients with COVID‐19?

Abstract: Objectives PNI is a calculated parameter using the albumin and the lymphocyte count from the CBC, which demonstrates the immunological and nutritional status of the patient. The aim of this study is to show the relationship between PNI and mortality in COVID‐19 patients and to reveal a PNI cut‐off value for mortality. Materials and Methods Data of 690 PCR positive COVID‐19 ICU patients were recorded. COVID‐19 ICU patients were divided into two groups; the first group consisted of survivors, while the second gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 26 publications
0
21
1
Order By: Relevance
“…Since its initial validation, its predictive capabilities have been documented in various clinical scenarios, including oncology [ 23 ], cardiology [ 24 ], and critical care [ 25 ]. In the setting of COVID-19, previously published articles have reported that a lower PNI score was associated with a more severe disease form [ 26 , 27 ] and higher COVID-19-related mortality [ 28 , 29 , 30 ]. The two previously reported cut-off values for predicting mortality were slightly discrepant, as one study suggested a cut-off below 33.4 [ 28 ], and the other 42 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its initial validation, its predictive capabilities have been documented in various clinical scenarios, including oncology [ 23 ], cardiology [ 24 ], and critical care [ 25 ]. In the setting of COVID-19, previously published articles have reported that a lower PNI score was associated with a more severe disease form [ 26 , 27 ] and higher COVID-19-related mortality [ 28 , 29 , 30 ]. The two previously reported cut-off values for predicting mortality were slightly discrepant, as one study suggested a cut-off below 33.4 [ 28 ], and the other 42 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of COVID-19, previously published articles have reported that a lower PNI score was associated with a more severe disease form [ 26 , 27 ] and higher COVID-19-related mortality [ 28 , 29 , 30 ]. The two previously reported cut-off values for predicting mortality were slightly discrepant, as one study suggested a cut-off below 33.4 [ 28 ], and the other 42 [ 30 ]. Our study’s cut-off value with the best discriminative capabilities (AUROC of 0.77) was 28, significantly lower than the other values.…”
Section: Discussionmentioning
confidence: 99%
“…Following the further exclusion of 144 records during screening of their titles and abstracts, six more articles were excluded after full-text assessment because of being a review article ( n = 1), abstract ( n = 3), lack of available outcomes ( n = 2), or focusing on disease progression instead of severity or mortality ( n = 1) [ 27 ]. Finally, 13 studies involving 4204 patients published between 2020–2021 were eligible for quantitative syntheses [ 11 , 19 , 20 , 21 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the studies are shown in Table 1 . Twelve studies reported the period for patient inclusion (i.e., all was conducted in 2020) [ 11 , 19 , 20 , 21 , 28 , 29 , 30 , 31 , 32 , 33 , 35 , 36 ], while one study did not provide this information [ 34 ]. The age of participants ranged from 44 to 74 years with the proportion of males between 42.3% and 61.5%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation